Research in Education of Children with Disabilities - Gowramma, Ittira Poovaiah; Gangmei, Elizabeth; Behera, Laxmidhar (INDIAN EDUCATIONAL REVIEW, 2018)
The review presents a systematic and comprehensive framework concerning the state of research in the field of education of children with disability/disabilities (CwD/CwDs) from the year 2000 to 2017, with a view to identify the key areas and generate questions for future research. Published studies, doctoral dissertations and institutional research were considered for mapping the current status. The analysis indicates that the area of study is expanding reflecting tremendous growth, research percolating various aspects of disability with a focus on empowering them through education. The time following the global flagship of Education for All (EFA) with a rights based approach for disability has made significant contribution to expansion of research ideas and scope. Fostering learning through various strategies, understanding the relationship of psychosocial factors in development and learning, academic performance, impact of significant people in development, and supporting learning through material development emerged as prominent choice of researchers. However, the analysis also shows that the research still seems to be considering disability as a deficit, and the need for shifting the focus to capacity approach by magnifying personal capabilities and dignity of CwD is strongly felt. There is paucity of researches based on critical perspective, serving both informative and transformative role. In order to fill the void empirical studies regarding the proactive measures that students with disability/disabilities (SwD) use to maximise their potential in personal, social and academic arena needs to be taken up in the future.